Body Heat - Kasdan, Lawrence, 1949-.; Preston, J. A.; Kathleen Turner; Kim Zimmer; Mickey Rourke; Richard Crenna; Ted Danson; William Hurt (USA Ladd Company, 1981)
Ned Racine is a seedy small town lawyer in Florida. During a searing heatwave he's picked up by married Matty Walker. A passionate affair commences but it isn't long before they realise the only thing standing in their way is Matty's rich husband Edmund. A plot hatches to kill him but will they pull it off?
In the midst of a searing Florida heat wave, a woman convinces her lover, a small-town lawyer, to murder her rich husband.
Lawrence Kasdan
Languages : English, German, Spanish Subtitles : English, Turkish, French, Spanish, Italian, Hebrew, Portuguese, Greek
Keywords: Drama; Thriller; Crime